2003
DOI: 10.1038/sj.sc.3101415
|View full text |Cite
|
Sign up to set email alerts
|

The role of upper limb surgery in tetraplegia

Abstract: Study design: A retrospective follow-up study. Objectives: To assess the value of surgery on the tetraplegic hand to improve its function. Setting: Spinal unit. Hospital La Fe. Valencia (Spain). Method: We reviewed the functional results obtained in 15 patients (10 males and 5 females) operated on at our hospital between 1988 and 1997. We performed 66 surgical procedures on 20 upper limbs. After a year or more the patients were evaluated by two independent examiners not related with the surgeons, using the que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 20 publications
1
21
0
1
Order By: Relevance
“…[1][2][3] Improvement in hand function is comparable to that of bladder and bowel function, which is known to have great impact on the lives of individuals with SCI. 4,5 In Denmark, ∼3000 people currently live with an SCI.…”
Section: Introductionmentioning
confidence: 73%
“…[1][2][3] Improvement in hand function is comparable to that of bladder and bowel function, which is known to have great impact on the lives of individuals with SCI. 4,5 In Denmark, ∼3000 people currently live with an SCI.…”
Section: Introductionmentioning
confidence: 73%
“…A possible explanation could be that the information given to them before the surgery was not precise, resulting in higher expectations. Forner-Cordero et al 11 found in their study that 57.2% of the persons expected better results of the surgery. Another possibility could be that there was really no improvement after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies report about satisfaction of participants as well, however, this is usually evaluated using only a few, untested questions. [11][12][13] These studies report that the majority of the participants are satisfied with the results of the surgery. Lo et al 12 described the outcome of tendon transfers for eight C6-spared quadriplegics (12 hands 15 The results of their study showed that 87.5% of their population were satisfied with the operation, 42.8% of the participants felt that the operation had fulfilled their expectations, however, 57.2% expected better results.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As this was a clinical notes audit on discharge information, it is unknown whether these people were offered the opportunity to be assessed but declined, or were never offered the opportunity. The average length of time between injury and surgery of 20 months is earlier in NZ compared with other countries such as Spain (34 months), 14 France (46.1 months) 15 and within the United States (34-50 months depending on the centre). [16][17][18] There are a number of plausible explanations for these observed differences between NZ and other countries.…”
Section: Discussionmentioning
confidence: 99%